Cover Feature: Isolation and Structure Determination of New Antibacterial Peptide Curacomycin Based on Genome Mining (Asian J. Org. Chem. 12/2017). Issue 12 (4th December 2017) - Kaweewan, Issara; Komaki, Hisayuki; Hemmi, Hikaru; Kodani, Shinya
Abstract : NRPS assembly line : The antibacterial peptide curacomycin was biosynthesized by nonribosomal peptide synthetases (NRPSs) and the unusual amino acid 5‐chlorotryptophan was synthesized by tryptophan halogenase. In order to find a new halogenated peptide, genome mining with focus on the halogenase gene existing near NRPS genes was performed. As a result, a new antibacterial peptide, named curacomycin, was isolated. As large genome data of bacteria are accumulated in public databases, the genome mining approach is a very powerful and efficient tool to find new bioactive compounds. More information can be found in the Full Paper by Shinya Kodani et al. on page 1838 in Issue 12, 2017 (DOI: 10.1002/ajoc.201700433 ).